The breeding population of rook "Corvus frugilegus" in major cities of Podlaskie voivodship (ne Poland) - Zbyryt, Adam; Polakowski, Michał (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Until now, there was no relevant data about the rook breeding populations in cities of north-eastern Poland. The main research was conducted in 2012, whereas in Białystok, which is the capital of Podlaskie voivodeship, the data was collected also in 2007. During the research 2329 nests forming 42 colonies were noted in three major cities, i..e. Białystok, Suwałki and Łomża. Mean density in mentioned cities was 5.17 pairs/ km2, 9.71 pairs/km2 and 33.09 pairs/km2 respectively.
Keywords: Rook; Corvus frugilegus; major cities; Podlaskie voivodeship; breeding colonies; nest